1976
DOI: 10.1007/bf00270863
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristics of collagen produced by long term cultivated amniotic fluid cells

Abstract: The synthesis of the most common type I of collagen was proven in human amniotic fluid cell culture with fibroblast morphology in the cells as well as in the culture medium. Mesenchymal origin of long term cultivated amniotic fluid cells is indicated and the possibility of prenatal investigation of hereditary disorders of connective tissue is pointed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…However, that study did not specify the identity of these cells. The presence of mesenchymal cells in the amniotic fluid has been suggested for decades [35,36]. Still, the progenitor identity of mesenchymal amniocytes started to be determined only very recently [21,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, that study did not specify the identity of these cells. The presence of mesenchymal cells in the amniotic fluid has been suggested for decades [35,36]. Still, the progenitor identity of mesenchymal amniocytes started to be determined only very recently [21,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…All epithelial surface cells that are in direct or indirect contact with the amniotic fluid have been considered as the sources of such cells including fetal epidermis, the epithelial cells of the respiratory, the urinary, and the intestinal tract of the fetus, and the epithelium of the "amniotic membrane" (Gerbie et al 1972;Hoehn et al 1975). The occurrence of cells with fibroblast-like morphology and detection of collagen type I in these cultures suggest that some of the clonable cells are true flbroblasts which stem from the connective tissue underlying the epithelial layers mentioned above (Macek et al 1973;Priest et al 1977;Hurych et al 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Addendum During preparation of this manuscript, there appeared a report (Hurych et al, 1976) presenting studies performed on one amniotic fluid culture 'after 19 weeks of cultivation'. From a determination of the chain ratio, the authors concluded that this culture synthesized type I collagen, and they then discussed possible applications to prenatal investigation of inherited disorders of collagen.…”
mentioning
confidence: 99%